Mode Competition and Radial Spread Analysis for Novel Double Beam Universal Electron Gun in 1.2 Terahertz Gyrotron - Singh A.S. (My University, 2025)
The generation of an electron beam and its interaction with RF wave is a decisive factor for gyrotron operation in the desired mode. Excitation of the desired mode primarily depends upon beam radius in addition to beam current. Therefore, a design investigation of the double beam electron optics system (DB-EOS) for 1.2 THz gyrotron is presented here, along with the mode competition study. The radial spread of the dual-beam magnetron injected gun is calculated to avoid the parasitic mode excitation and ensure the isolation between the inner and outer beams. Furthermore, this study is extended to investigate the velocity spread variation over emitter roughness and cathode temperature. This study finds that radial spread should be below 0.04 mm for the internal beam to avoid competition and TE-85 mode is severely competing with operating TE21,4 and TE-15,6 mode for external beam. © 2021 IEEE.